2022
DOI: 10.1039/d2gc00196a
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis to prepare lignin/photoacid nanohybrids for multifunctional biosensors and photo-triggered singlet oxygen generation

Abstract: This study presents a green, simple, and efficient one-pot synthesis approach for a sustainable lignin nanoparticle biosensor (AL-Por-PP). Lignin was incorporated with a typical 5-5’ linkage interunit for developing azo-coupling...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…These characteristics grant lignin a range of unique optical properties, including aggregation-induced luminescence, UV absorption, and sustainable photothermal conversion, among others. 124,125 Several reports have explored the coupling of lignin with photosensitive groups, 126–128 some of which revealed its potential for preparing photo-responsive materials. 126 However, its application in drug delivery is relatively scarce.…”
Section: Promising and Underexploited Intelligent Lcrfs: Potentials A...mentioning
confidence: 99%
“…These characteristics grant lignin a range of unique optical properties, including aggregation-induced luminescence, UV absorption, and sustainable photothermal conversion, among others. 124,125 Several reports have explored the coupling of lignin with photosensitive groups, 126–128 some of which revealed its potential for preparing photo-responsive materials. 126 However, its application in drug delivery is relatively scarce.…”
Section: Promising and Underexploited Intelligent Lcrfs: Potentials A...mentioning
confidence: 99%
“…4 This noncontact trigger method and reversible proton transfer process promise the easy application of photoacid-based materials in different fields. Different types of metastable-state photoacids possess different applications, such as catalysis, 4 sensors, 5 molecular switches, 6 conductivity, 7 antibacterial, 8 supramolecular assemblies, 9 and photochromism. 10 The most common photoacids include spiropyran/merocyanine, tricyanofuran, and pyranine derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This limitation is overcome by expensive pyrolytic techniques associated with high-temperature treatments (500–1300 °C). The self-assembly of lignin into ordered nanoparticles (LNPs) can be a promising alternative to traditional approaches due to the emergence of beneficial chemophysical, rheological, and electrochemical properties as a consequence of the supramolecular organization of the aromatic subunits of the polymer . It includes π–π HOMO–LUMO interactions with the formation of head-to-tail (J-type) and tail-to-tail (H-type) aggregates and the emergence of unprecedented electron-transfer behaviors. Currently, the applications of LNPs in biosensing are still limited to phototriggered and photoluminescence devices based on the immobilization of redox enzymes. In the latter case, the boosting effect associated with long-range electron-transfer (pseudo-DET) and mediated electron-transfer (MET) processes were reported and discussed in detail, focusing on the role played by low-molecular-weight mediators as diffusible shuttles from the enzyme to the bulk of the solution. ,, In principle, the HOMO–LUMO energy gap in LNPs may be controlled by the selection of the starting lignin as well as by the presence of other polymers, such as polysaccharides. ,, Polysaccharides act as spacers and structural orienting motifs in lignin aggregation, their effect being dependent on the deacetylation degree and molecular weight of the molecule . We recently reported that the HOMO–LUMO energy gap in lignin–chitooligosaccaride nanoparticles is modulated by the saccharide component .…”
Section: Introductionmentioning
confidence: 99%